PERAN PROMOSI JABATAN TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN (Studi pada PT. Star Comgistic Indonesia Kabupaten Sukabumi) - Rismayanti, fani; Mulia, Faizal; Komariah, Kokom (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.NO.03.TAHUN 2020DO - 10.24843/EEB.2020.v09.i03.p05, 2020)
This research was conducted at PT. Star Comgistic Indonesia Sukabumi Regency which aims to find out the role of promotion in the work productivity improvement. The samples used were as many as 90 people / respondents taken at random. Sources of data obtained were using interview techniques and questionnaires. The method used in this research is descriptive and associative by using a quantitative approach. The results of the t-test study on the promotion promotion variable showed the t-value in this study was 5.733 with a significant value of 0.000, a significant value of 0.000 was smaller than 0.05 (0.000 <0.05). So the results of this study indicate that the role of promotion in increasing work productivity has a positive and significant.